DENSIDADE DE POTÊNCIA INSTALADA LIMITE DO RTQ-C: ANÁLISE DE AMBIENTES COM CLASSIFICAÇÃO D E E - Peixoto, Luiza Barrio; Veloso, Ana Carolina Oliveira; Souza, Roberta Vieira Gonçalves de (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The energy consciuos consumption is a recurrent subject in many sectors and countries. The concern about buildings energy efficiency in Brazil became a reality with RTQ-C (Regulamento Técnico da Qualidade do nÍvel de Eficiência Energética de Edifícios Comerciais, de Serviços e Públicos). The artificial lighting sistem corresponds to 30% of the maximum score in this method. With the application of this method it was verified that activities in small areas get low ratings, D and E. This work has the main objective to search in the sample of buildings with same laboratory consultancy to get the PBE Edifica Tag which are the activities with low ratings, D and E and if the LPD limits are adequate with its realities. The study showed that bathrooms were the most problematic activity with 85,8% of the sample with low rating, E. It was verified, compared to ASHARE 90.1 that the limits on RTQ-C are very restrictive for some activities given the reality of used technologies. Therefore, the limits should be reviewed based on the areas and lighting sistem most commons at the buildings.